On Methods of Controlling Optimization Software Packages with the Application of Parallel Computing - Aidazade, K.R.; Guliyev, S.Z. (Математичне та комп'ютерне моделювання. Серія: Фізико-математичні науки, 2017)
The paper is dedicated to the analysis of methods and algorithms of controlling computational process of solving complex problems with the use of multiprocessor and/or multicore computer systems. We have developed an automatic and dialogue systems of control of unconstrained optimization process, which have a graphical user interface.